2013
DOI: 10.1093/mp/sss120
|View full text |Cite
|
Sign up to set email alerts
|

How Do Sugars Regulate Plant Growth and Development? New Insight into the Role of Trehalose-6-Phosphate

Abstract: Plant growth and development are tightly controlled in response to environmental conditions that influence the availability of photosynthetic carbon in the form of sucrose. Trehalose-6-phosphate (T6P), the precursor of trehalose in the biosynthetic pathway, is an important signaling metabolite that is involved in the regulation of plant growth and development in response to carbon availability. In addition to the plant's own pathway for trehalose synthesis, formation of T6P or trehalose by pathogens can result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
167
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(194 citation statements)
references
References 110 publications
4
167
0
4
Order By: Relevance
“…T6P synthase is involved in the biosynthesis of T6P and trehalose, both having important functions in plant growth and development. Trehalose is an osmoprotectant that influences maize inflorescence architecture, whereas T6P is an important signaling molecule involved in embryo development, vegetative growth, and leaf senescence (O'Hara et al, 2013). Also, the presence of a GIBBERELLIN 20-OXIDASE2 ortholog (GRMZM2G099467), which is hypermethylated in the TZ, was notable, as our previous experiments revealed a pivotal role for GAs in maize leaf development, specifically in the TZ (Nelissen et al, 2012).…”
Section: Many Differentially Methylated Genes Are Involved In Gene Rementioning
confidence: 80%
See 1 more Smart Citation
“…T6P synthase is involved in the biosynthesis of T6P and trehalose, both having important functions in plant growth and development. Trehalose is an osmoprotectant that influences maize inflorescence architecture, whereas T6P is an important signaling molecule involved in embryo development, vegetative growth, and leaf senescence (O'Hara et al, 2013). Also, the presence of a GIBBERELLIN 20-OXIDASE2 ortholog (GRMZM2G099467), which is hypermethylated in the TZ, was notable, as our previous experiments revealed a pivotal role for GAs in maize leaf development, specifically in the TZ (Nelissen et al, 2012).…”
Section: Many Differentially Methylated Genes Are Involved In Gene Rementioning
confidence: 80%
“…For example, GRMZM2G311883 is a gene homologous to Arabidopsis MODIFIER OF SNC1-1 14 (MOS14), which is known to form a link between splicing and RNAdependent DNA methylation . Also, genes involved in cell cycle regulation, such as CYCD4, APC10, TIP120-encoding (Wang et al, 2011b), FORMIN8-like (Xue et al, 2011), and AUGMIN6-like (Hotta et al, 2012), are represented in the data set, as are developmental processes affecting the vasculature (Petricka et al, 2008), meristem maintenance , and cell shape and plant architecture (O'Hara et al, 2013). Several genes that are differentially methylated in the older zones play a known role in development.…”
Section: Differential Methylation Along the Developing Maize Leaf Potmentioning
confidence: 99%
“…Trehalose is a disaccharide, which is found in the majority of plants in only trace amounts and has been thought to control basic plant processes as well as being involved in resistance to abiotic stress factors and signalling. More recent work is now showing that it is trehalose‐6‐phosphate, a precursor of trehalose, which is the signalling molecule (Paul et al , 2008; O'Hara et al , 2013) and interestingly it has been shown that treating wheat with trehalose can induce partial protection against the powdery mildew pathogen ( Blumeria graminis ), which could be because of the activation of defence responses (Reignault et al , 2001; Tayeh et al , 2014). Trehalose is important to insects, as the starting point in chitin synthesis (Paul et al , 2008) and is known to occur in the haemolymph of the aphids Megoura viciae and Acyrthosiphon pisum (Rhodes et al , 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The saliva of D. noxia , A. pisum and Phlebotomus arabicus has been found to contain trehalase, which converts trehalose to two glucose molecules and it has been suggested that the role of trehalase in the saliva of the aphids is to disrupt the stress response signalling by the plant (Nicholson et al , 2012; Hodge et al , 2013). Another suggested role could be that the aphids are able to interfere with the sugar sensing pathway of the plant, manipulating it in their favour as has been suggested with plant pathogens (O'Hara et al , 2013). Thus, our finding of elevated trehalose in resistant wheat warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent reviews on the role of sugar signaling in plant development have been published in recent years. Most of these focus on specific signaling pathways or developmental processes, for example, on flowering and interaction with hormones (Matsoukas, 2014a), growth (Lastdrager et al, 2014), T6P (O'Hara et al, 2013), T6P and SnRK1 (Tsai and Gazzarrini, 2014), hexokinase (Granot et al, 2014), miRNAs (Yu et al, 2015), or SnRK1 and TOR (Baena-González and Hanson, 2017). The whole life cycle of the plant is considered here (Box 1), including step changes (such as floral transition) as well as more gradual processes (such as leaf senescence).…”
mentioning
confidence: 99%